Immigration, Innovation, and Growth - Terry, Stephen J.; Chaney, Thomas; Burchardi, Konrad B.; Tarquinio, Lisa; Hassan, Tarek A. (American Economic Review, 2026)
We propose a novel identification strategy to isolate exogenous immigration shocks across US counties, by interacting quasi-random variations in the composition of ancestry across counties with the contemporaneous inflow of migrants from different countries. We show a positive causal impact of immigration on local innovation and wages at the five-year horizon. The positive dynamic impact of immigration on innovation and wages dominates the short-run negative impact of increased labor supply. A structural estimation of a model of endogenous growth and migrations suggests the increased immigration to the United States since 1965 may have increased innovation and wages by 5 percent. (JEL J15, J22, J31, J61, O31, R11, R23)